Palaeoethnobotany - Lone, Farooq A., author.
1 online resource.
Keywords: A study of the palaeoethnobotany of Kashmir, covering covers the period from 4500 BP to 1000 BP. It includes keys to the identification of various species of Triticum, Hordeum, Avena and Prunus, and hard and soft woods, and lists the criteria for identification of weed seeds of some 200 species.